Komposisi Tanaman Penyusun Agroforestri Dalam Mendorong Peningkatan Ekonomi Masyarakat di Desa Bilalang Baru - Hendra Amon; Robby DJ Rempas; Hardiana F Paputungan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Changes in the landscape and management of natural resources from forest areas to agricultural land are currently an issue, so agroforestry is the right concept to apply to converted land.. The concept of agroforestry offers a solution, whereby the implementation of agroforestry is a land use system that integrates forestry and agricultural crops to create balanced ecological conditions, economic benefits, and local wisdom within the community. The community of Bilalang Baru Village has implemented an agroforestry system with a composition of plants aimed at boosting the community's economy. The purpose of this study is to identify the composition of agroforestry plants in promoting economic improvement in the community. The research method used was descriptive qualitative and quantitative through the exploration of data and facts in the field. Data collection methods included in-depth interviews, observation, and literature study. The results showed that the composition of plant species in agroforestry to promote economic improvement in the Bilalang Baru community was found in agroforestry land consisting of 3 types of timber forestry plants, 8 types of fruit plants, 3 types of industrial plants, 3 types of industrial plants, 2 types of cereal plants, 8 types of vegetable plants, 3 types of tuber plants, and 5 types of rhizome plants.